Magnetic Resonance Imaging (MRI) Based Diagnosis of Anterior Cruciate Ligament (ACL) TEARS in Patients with Internal Derangements of Knee - Rahim, Reshyl; Balooch, Salahuddin; Usman Khan, Muhammad; Bokhari, Syed Awon Raza Shah; Baqir Hassan, Khawaja Muhammad; Niazi, Najam Us Saqib (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the role of magnetic resonance imaging (MRI) in diagnosing anterior cruciate ligament (ACL) tears in patients with knee internal derangements.Study Design: Prospective longitudinal study.Place and Duration of Study: Department of Radiology, Combined Military Hospital, Kharian Pakistan, from Sep 2019 Aug 2020.Methodology: 40 patients of any age and gender were part of the study with painful or unstable knee joints. A clinical examination was performed after recording demographic data. In addition, MRI was performed, and primary and secondary signs were noted for each case.Results: The range of patients was 15 to 63, with a mean age of 36.3 ± 12.62 years. Most of the patients were male (n=29; 72.5%), whereas only 11 (27.5%) were females. In total, 27 (67.5%) complete and 13 (32.5%) partial Anterior cruciate ligament (ACL) tears were present. Blumensaat’s angle> 15 degree was present in 10 (37.03%) complete tear cases and 2 (15.38 %) partial tear cases. Anterior tibial displacement was evident in 4 (14.81%) complete tear cases and 3 (23.07 %) partial tear cases. Posterior cruciate line (PCL) angle was apparent in 21 (77.77%) complete tear cases and 12 (92.30 %) partial tear cases.Conclusion: The use of MRI is advocated for diagnosing Anterior cruciate ligament (ACL) tears in patients with knee internal derangements.